A novel SSI-based optimization framework for non-traditional TMDI system under near- and far-fault ground motions - Onur Araz; Davide Forcellini (Soil Dynamics and Earthquake Engineering, 2026)

A closed-form approach to assess the mutual effects between base isolation (BI) and soil-structure interaction (SSI) - Davide Forcellini; Konstantinos N. Kalfas (Soil Dynamics and Earthquake Engineering, 2026)

Seismic resilience assessment of pile groups against liquefaction-induced lateral spreading: Influence of ground inclination and pile spacing - Davide Forcellini; Faramarz Ranjbar; Ali Asgari; Mohsen Bagheri; Hessam Yazdani (Engineering Structures, 2026)

Dynamic centrifuge modeling on the superstructure–pile system considering pile–pile cap connections in dry sandy soils - Gang Zheng; Wenbin Zhang; Davide Forcellini; Haizuo Zhou; Jihui Zhao (Soil Dynamics and Earthquake Engineering, 2024)

Seismic fragility assessment of geotechnical seismic isolation (GSI) for bridge configuration - Davide Forcellini; Saif Alzabeebee (Bulletin of Earthquake Engineering, 2023)
The seismic vulnerability of bridges may be reduced by the application of Geotechnical Seismic Isolation (GSI) below the foundations of the columns and the abutments. However, the role of GSI on the seismic response of bridges has been limitedly examined in literature. Therefore, this research has been conducted to study the effect of applying GSI on the seismic response of bridges to address the aforementioned gap in knowledge. Advanced nonlinear dynamic three-dimensional finite element analyses have been conducted using OpenSees to study the influence of the GSI. The cases of traditional and isolated bridges subjected to earthquakes have been considered to assess the GSI effects. The results showed that the GSI reduces the seismic effect on the column while its effect seems to be less significant for the abutments. In addition, fragility curves for the traditional and isolated cases have been developed and compared to provide insights with a probabilistic-based approach. The results of this paper provide a useful benchmark for design considerations regarding the use of GSI for bridges.

Resilience of HP/HT pipelines to combined seismic and thermal loadings - Daniele Mina; Hassan Karampour; Davide Forcellini (Ocean Engineering, 2023)

Seismic resilience of bridges isolated with traditional and geotechnical seismic isolation (GSI) - Davide Forcellini (Bulletin of Earthquake Engineering, 2023)

The role of soil structure interaction (SSI) on seismic response of tall buildings with variable embedded depths by experimental and numerical approaches - Mohammed El Hoseny; Jianxun Ma; Walid Dawoud; Davide Forcellini (Soil Dynamics and Earthquake Engineering, 2023)

Inter-story seismic isolation for high-rise buildings - Davide Forcellini; Konstantinos N. Kalfas (Engineering Structures, 2023)

The Role of Soil Structure Interaction in the Fragility Assessment of HP/HT Unburied Subsea Pipelines - Davide Forcellini; Daniele Mina; Hassan Karampour (Journal of Marine Science and Engineering, 2022)
Subsea high pressure/high temperature (HP/HT) pipelines may be significantly affected by the effects of soil structure interaction (SSI) when subjected to earthquakes. Numerical simulations are herein applied to assess the role of soil deformability on the seismic vulnerability of an unburied pipeline. Overcoming most of the contributions existing in the literature, this paper proposes a comprehensive 3D model of the system (soil + pipeline) by performing OpenSees that allows the representation of non-linear mechanisms of the soil and may realistically assess the induced damage caused by the mutual interaction of buckling and seismic loads. Analytical fragility curves are herein derived to evaluate the role of soil structure interaction in the assessment of the vulnerability of a benchmark HP/HT unburied subsea pipeline. The probability of exceeding selected limit states was based on the definition of credited failure criteria.

Seismic assessment of the historical third tower in San Marino based on a 3D laser scanner survey (3D-LSS) - Davide Forcellini; Fabrizio Giardi; Marco Tanganelli (Innovative Infrastructure Solutions, 2019)

A new methodology to assess indirect losses in bridges subjected to multiple hazards - Davide Forcellini (Innovative Infrastructure Solutions, 2019)

Numerical simulations of liquefaction on an ordinary building during Italian (20 May 2012) earthquake - Davide Forcellini (Bulletin of Earthquake Engineering, 2019)

Seismic assessment of storey isolation on tall buildings - Davide Forcellini; Luca Gallanti (Innovative Infrastructure Solutions, 2018)

Seismic assessment of a benchmark based isolated ordinary building with soil structure interaction - Davide Forcellini (Bulletin of Earthquake Engineering, 2018)

Assessment on geotechnical seismic isolation (GSI) on bridge configurations - Davide Forcellini (Innovative Infrastructure Solutions, 2017)

Seismic resilience of isolated bridge configurations with soil–structure interaction - Davide Forcellini (Innovative Infrastructure Solutions, 2017)

Cost assessment of isolation technique applied to a benchmark bridge with soil structure interaction - Davide Forcellini (Bulletin of Earthquake Engineering, 2017)

3D Numerical simulations of elastomeric bearings for bridges - Davide Forcellini (Innovative Infrastructure Solutions, 2016)
Multilayer elastomeric isolation can be considered a well-known solution with many applications in the last 20 years in the infrastructure arena. In particular, isolation has been extensively applied for pier and abutment protection, in order to strengthen bridges against earthquakes. Elastomeric bearings can be subjected to large axial loads and lateral displacements during strong earthquakes, which induce potentially buckling effects. The recent Forcellini and Kelly (J Eng Mech 140(6):04014036, 2014) model allows to take into account large deformation response of a bearing when buckling occurs. This paper aims at verifying this theory using experimental results and numerical simulations. First of all, test results are taken from Nagarajaiah and Ferrell (J Struct Eng 125:946–954, 1999) and compared with the developed theory. Then, numerical simulations have been performed by applying OpenSees.